KEMAMPUAN MEMPARAFRASAKAN PUISI SURAT DARI IBU KE DALAM KARANGAN NARATIF - Haris Nur Prasetyo; Kahfie Nazaruddin; Ali Mustofa (FKIP Universitas Lampung, 2015)
The purpose of this study is to describe the ability to paraphrase a poem into a narrative essay in class X SMA Negeri 1 Talangpadang academic year 2014/2015. Based on the analysis, the value of (a) the suitability aspect of the theme is quite with an average score of 69.02; (b) aspects of the essay title selection is quite with an average score of 62.84; (c) the principal aspects of the unity between the sentence and the sentence is quite explanatory in the essay with an average score of 67.95; and (d) aspects of the elements of a narrative essay is quite builder with an average score of 64.56.Tujuan penelitian ini adalah mendeskripsikan kemampuan memparafrasakan puisi ke dalam sebuah karangan naratif pada siswa kelas X SMA Negeri 1 Talangpadang tahun pelajaran 2014/2015. Berdasarkan hasil analisis, diperoleh nilai (a) aspek kesesuaian tema tergolong cukup dengan skor rata-rata 69,02; (b) aspek pemilihan judul karangan tergolong cukup dengan skor rata-rata 62,84; (c) aspek kesatuan antara kalimat pokok dan kalimat penjelas dalam karangan tergolong cukup dengan skor rata-rata 67,95; dan (d) aspek unsur-unsur pembangun karangan naratif tergolong cukup dengan skor rata-rata 64,56.Kata kunci: naratif, parafrasa, puisi.